Co-designing platform collectivism. Issue 3 (3rd July 2019) - Carroll, John M.; Beck, Jordan
ABSTRACT: We report a codesign effort to envision a community water quality data platform with local stakeholders. We employed interviews, field observations, and hackathons through a 9-month study (ongoing). This codesign effort helps to distinguish our proposal of platform collectivism, in which local resources and stakeholders become more visible, accessible, and engaged with one another through the development and use of a community-based open data platform. In addition, we synthesize key insights for codesign. In our project, local stakeholders have an significant stake in the research and design work. They pose research questions, set goals, and establish parameters for collaboration with us.